Moment of Action : Riddles of Cinematic Performance - Pomerance, Murray, 1946- (Book collections on Project MUSE., 2016)
Moment of Action delves into the mysteries of screen performance, revealing both the acting techniques and the technical apparatuses that coalesce in an instant of cinematic alchemy to create movie gold. Considering a range of acting styles while examining films as varied as Bringing Up Baby, Psycho, The Red Shoes, Godzilla, and The Bourne Identity, Murray Pomerance takes us on an innovative exploration of the nexus at which the actor's keen skills spark and kindle the audience's receptive energies.